Risk Factors for Recurrent Tracheoesophageal Fistula After Gross Type C Esophageal Atresia Repair - Yang, Shen; Li, Siqi; Yang, Zhi; Liao, Junmin; Hua, Kaiyun; Zhang, Yanan; Zhao, Yong; Gu, Yichao; Li, Shuangshuang; Huang, Jinshi (Frontiers in Pediatrics, 2021)
Background: To determine the possible risk factors of recurrent tracheoesophageal fistula (rTEF) after Gross type C esophageal atresia (EA) and tracheoesophageal fistula (TEF) repair. Methods：The medical records of 343 pediatric patients with Gross type C EA/TEF who underwent surgical repair were retrospectively analyzed. The patients were retrospectively divided into 2 groups according to whether they had rTEF. Univariate and multivariable logistic regression analysis were performed to identify risk factors for rTEF. Results: After the diagnosis of EA/TEF, 343 patients (221 boys) underwent primary repairs after birth. The primary operations were performed via thoracoscopic or open approach. According to the follow-up results, 259 patients (257 survived and 2 died after rTEF repair) were included in the analysis. rTEF occurred in 33 patients (33/259, 12.74%), with a median onset time to recurrence of 3.8 (2.2, 8.2) months. Univariate analysis showed that method for fistula closure (P = 0.044) and the length of hospital stay (P = 0.009) were associated with rTEF. Multivariate analysis showed that closing the fistula with ligation and hospital stay ≥ 28.5 days were significant risk factors of rTEF with OR of 4.083 (1.481, 11.261) and 3.228 (1.431, 7.282). Conclusions: Closing the fistula with ligation and hospital stay ≥ 28.5 days were significant risk factors of rTEF after Gross type C EA/TEF repair.